Biological and Climate Controls on North Atlantic Marine Carbon Dynamics Over the Last Millennium: Insights From an Absolutely Dated Shell‐Based Record From the North Icelandic Shelf. Issue 12 (28th December 2017) - Reynolds, D. J.; Hall, I. R.; Scourse, J. D.; Richardson, C. A.; Wanamaker, A. D.; Butler, P. G.
Abstract: Given the rapid increase in atmospheric carbon dioxide concentrations ( p CO2 ) over the industrial era, there is a pressing need to construct long‐term records of natural carbon cycling prior to this perturbation and to develop a more robust understanding of the role the oceans play in the sequestration of atmospheric carbon. Here we reconstruct the past biological and climate controls on the carbon isotopic (δ 13 Cshell ) composition of the North Icelandic shelf waters over the last millennium, derived from the shells of the long‐lived marine bivalve mollusk Arctica islandica. Variability in the annually resolved δ 13 Cshell record is dominated by multidecadal variability with a negative trend (−0.003 ± 0.002‰ yr −1 ) over the industrial era (1800–2000 Common Era). This trend is consistent with the marine Suess effect brought about by the sequestration of isotopically light carbon (δ 13 C of CO2 ) derived from the burning of fossil fuels. Comparison of the δ 13 Cshell record with Contemporaneous proxy archives, over the last millennium, and instrumental data over the twentieth century, highlights that both biological (primary production) and physical environmental factors, such as relative shifts in the proportion of Subpolar Mode Waters and Arctic Intermediate Waters entrained onto the North Icelandic shelf, atmospheric circulation patterns associated with the winter North Atlantic Oscillation, and sea surface temperature and salinity of the subpolar gyre, are the likely mechanisms that contribute to natural variations in seawater δ 13 C variability on the North Icelandic shelf. Contrasting δ 13 C fractionation processes associated with these biological and physical mechanisms likely cause the attenuated marine Suess effect signal at this locality. Key Points: We evaluate the drivers of variability in an annually resolved absolutely dated marine δ13C record that spans the entire last millennium The δ13C record contains significant multidecadal variability, which significantly changes period between the Medieval Climate Anomaly and Little Ice Age Water mass dynamics, atmospheric circulation (winter North Atlantic Oscillation), and changes in productivity are the likely mechanisms that drive the δ13C variability